All‐Dielectric Meta‐Optics for High‐Efficiency Independent Amplitude and Phase Manipulation. Issue 3 (26th December 2021) - Raeker, Brian O.; Zheng, Hanyu; Zhou, You; Kravchenko, Ivan I.; Valentine, Jason; Grbic, Anthony
Abstract : Optical metasurfaces, composed of subwavelength scattering elements, demonstrate remarkable control over the transmitted amplitude, phase, and polarization of light. However, manipulating the amplitude upon transmission, without the use of surface waves, requires loss if a single metasurface is used. Herein, high‐efficiency independent manipulation of the amplitude and phase of a beam is described using two lossless phase‐only metasurfaces separated by a distance. With this configuration, optical components such as combined beam‐forming and splitting devices are experimentally demonstrated, as well as those for forming complex‐valued, 3D holograms. The compound meta‐optic platform provides a promising approach for achieving high‐performance holographic displays and compact optical components, while exhibiting a high overall efficiency. Abstract : High‐efficiency independent manipulation of an optical beam amplitude and phase profile is experimentally shown using two phase‐only metasurfaces separated by a distance, forming a meta‐optic. A combined beam‐forming and splitting function and displaying 3D holograms are demonstrated. The meta‐optic platform provides a promising approach for applications requiring detailed field control, while exhibiting a high overall efficiency.